Lawyering at the Intersection of Mediation and Community Economic Development: Interweaving Inclusive Legal Problem Solving Skills in the Training of Effective Lawyers - Beryl Blaustone; Carmen Huertas-Noble (Washington University Journal of Law & Policy, 2010)
In this Essay, Beryl Blaustone and Carmen Huertas-Noble insightfully explore the intersections between community economic development (CED) legal practice and mediation. They suggest that CED lawyers and mediators frequently engage in parallel roles and employ similar skill sets to foster creative problem solving, empower clients and client communities, and advance the interests of all the parties. In their view, both CED lawyers and mediators should engage in what the authors call "inclusive problem-solving," an overlapping skill set that includes metacognitive self-awareness; robust information gathering and focusing with clients; and reframing positions, framing issues,and generating options that maximize the group’s shared interest in order to increase the gains for the entire group. Using a hypothetical case study, the authors present a useful, clarifying discussion of "what we do" and "how we do it" for each of the three categories. For Blaustone and Huertas-Noble, the cornerstone of inclusive problem-solving is metacognitive self-awareness, a deliberate process where the professional focuses on critically listening to their internal thoughts in order to control their clinical judgment. The authors are highly critical of the lack of a consistent, rigorous pedagogy for embedding in law students a metacognitive awareness that provides an internal monitor that questions the basic inclination to perceive and gather data that supports one's belief structure while neglecting evidence to the contrary and ignoring alternative interpretations.
Keywords: Urban planning; Sustainable development; Mediation; Problem solving; Clinical legal education; Arbitrators; Economic development; Lawyers